EXPANSION, ECOLOGIZATION OF SAINFOIN CROPS, AND DEVELOPMENT OF A MOLECULAR-GENETIC ALGORITHM FOR SAINFOIN IN THE ALMATY REGION (Experimental biology, 2025)
This review article addresses a key issue in crop production in the Almaty region: the need to ensure an adequate supply of quality plant (forage) protein. Sainfoin (Onobrychis spp.), as a promising source of forage protein, offers a wide range of agronomic and ecological benefits for future applications in agriculture and medicine. The article provides an overview of forage legumes, details the biological and physiological features of sainfoin, and highlights its role in enhancing biotic resistance. Additionally, it assesses the nutritional properties of sainfoin, evaluates feed and feed additive quality based on sain- foin, and examines its contribution to reducing nitrogen fertilizer costs and improving soil fertility. The review is based on a detailed analysis of Onobrychis spp., emphasizing its potential to support human and animal health through essential amino acids, unsaturated fatty acids, micronutrients, and antinutri- tional compounds, including tannins. Special attention is given to the potential of symbiotic interactions between Onobrychis spp. and nitrogen-fixing bacteria of the genus Rhizobium and the search for new unique strains suited for sainfoin. Research in Southeastern Kazakhstan is anticipated to yield new sain- foin varieties, enriching the forage legume range. Sainfoin is underscored as a valuable protein-enriched feed for livestock. This crop is also projected to contribute to public health as a low-calorie food option for combating obesity and cardiovascular diseases. In conclusion, the article emphasizes that advancing sainfoin research could provide balanced food and feed products based on this crop, promoting signifi- cant quality improvements in crop and livestock production.
Keywords: sainfoin, Onobrychis spp., feed additives, food security.